Multigram Synthesis of Thallium Trispyrazolylborate Compounds - Olmos, Andrea; Pereira, Ana; Belderrain, Tomás R.; Pérez, Pedro J. (Synthesis, 2018)
A multigram method for the preparation of thallium trispyrazolylborate complexes is described.
Keywords: hydrotrispyrazolylborates; thallium(I) complexes; scorpionate ligands; thallium borohydride; multigram synthesis